(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Healthcare organizations strive for quality in their service delivery as a way of keeping up with the competing trends in clients’ attraction. In the process, they have become cognizant of the key performance indicators to help track progress and performance. Despite the growing interests in healthcare KPIs, little has been done in terms of KPIs in the general hospitals, especially in the critical care units. Therefore, this study was designed to assess the implications of KPIs on the quality of healthcare service delivery in the critical care department in a general hospital in the Kingdom of Saudi Arabia. Methods: Quantitative descriptive quantitative research was conducted a among 300 healthcare workers in the critical care unit of a general hospital in Saudi Arabia. Data was collected after receiving ethical approval and participants’ consent. Accordingly, the researcher administered the questionnaires to the selected participants using a pre-made research questionnaire using the 5-point Likert scale. The collected data was analyzed using linear regression and the descriptive statistical tests of SPSS, version 26. Results: From the descriptive statistical analysis, two key performance indictors outstood in the critical care department of general hospitals. These include experiences with hospital staff (mean=3.143; SD =2.00) and Patient Readmission Rate (mean=3.106; SD=1.419). A statistically significant relationship was also noted between patient readmission rate (p=.030), experiences with hospital staff (p=.070) and staff’s commitment to patients (p=.016) and the quality of critical care care services. Conclusion: Key performance indicators are crucial in tracking the milestones made in healthcare organizations towards meeting patients’ needs. Healthcare system management need to develop a means of tracking their key performance indicators for informed improvements in quality of their services.